Comparison of Regulatory Requirements for Pharmaceuticals in Non- European Union Member States Kosovo, Ukraine and Serbia - Jani, Shivani; Patel, Nilesh; Chotaliya, Urvi; Patel, Ashok (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2020)
Background: Literature review suggested that regulatory guidelines should be harmonized for better processing of applications and for the upliftment of the regulatory field. Therefore it was thought worthwhile to compare the guidelines for countries where there is requirement of harmonization. Kosovo, Ukraine and Serbia were selected because of being European countries and still they are not a part of EU. Introduction: Kosovo, Ukraine and Serbia are small countries of Europe but they are not members of European Union. They have their own guidelines for the submission of MAA for marketing of pharmaceuticals and medical devices. They are trying to obtain the EU membership and therefore it was worthwhile to compare the guidelines of these countries. Methods: The registration process of pharmaceuticals in Kosovo, Ukraine and Serbia was studied throughly. Along with it, the guidelines for European Union were also studied. A comparison of guidelines of all the three countries with the guidelines of European Union for pharmaceuticals was carried out. Results: The comparison of guidelines showed that there are still some changes needed in the guidelines of Kosovo, Ukraine and Serbia before they can merge with the guidelines of European Union. Some of the points in the guidelines are very different from the guidelines of EU. Conclusion: It was worthwhile to study the regulatory requirements of pharmaceuticals in Non- European Union Member States such as Kosovo, Ukraine and Serbia.
Keywords: Kosovo